2022
DOI: 10.3390/su14084678
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Irresponsibility Punishments from Stakeholders—Evidence from China

Abstract: Corporate social irresponsibility (CSIR) scandals are frequently reported in China and have a huge impact on the enterprise and society. Aiming to understand the underlying mechanisms between CSIR and enterprise outcomes, this study uses a sample of 2618 firms from the 2018 National Survey of Private Entrepreneurs Survey and examines the corporate social irresponsibility punishments from the perspective of stakeholders by introducing transaction costs. The results indicate that although the punishments for cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Kang et al (2016) [66] find that the insurance mechanism (i.e., CSR ensures against subsequent CSIR) is not supported, but the penance mechanism (i.e., CSR trails the firm's prior CSIR) is supported. However, this study also suggests that "the penance mechanism is ineffective in offsetting negative performance effect due to CSIR" (p. 59).…”
Section: Literature Reviewmentioning
confidence: 72%
See 1 more Smart Citation
“…Kang et al (2016) [66] find that the insurance mechanism (i.e., CSR ensures against subsequent CSIR) is not supported, but the penance mechanism (i.e., CSR trails the firm's prior CSIR) is supported. However, this study also suggests that "the penance mechanism is ineffective in offsetting negative performance effect due to CSIR" (p. 59).…”
Section: Literature Reviewmentioning
confidence: 72%
“…For instance, Stewart (2016) [57] found that CSIR predicts higher CFP in the subsequent year, as CSIR activities offer firms cost advantages. However, once CSIR is disclosed, these advantages vanish, leading to a negative long-term CSIR-CFP relationship [58,59]. Disclosed CSIR can lead to increased media scrutiny, impaired stakeholder relationships, reputational damage, and financial risks [13,[60][61][62].…”
Section: Literature Reviewmentioning
confidence: 99%
“…5. Also, specific consequences call for attention as Feng et al (2022) evidence for transaction costs.…”
Section: Notesmentioning
confidence: 99%
“…Antonetti, 2020;Valor et al, 2022), in firms' financial performance as well as in firms' reputation, trustworthiness and moral capital (e.g. Sun and Ding, 2021;Wang and Li, 2019), in firm's transaction costs (Feng et al, 2022) and in workplace deviant behaviors as a form of employee revenge (Abbasi and Amran, 2023). These important and far-reaching consequences may explain the increased interest of researchers and practitioners in understanding CSI antecedents [1].…”
Section: Introductionmentioning
confidence: 99%